Pengaruh Latihan Power Otot Lengan Push Up Dumbell Swing Dan Hand Walking Terhadap Kecepatan Renang Gaya Bebas 50 Meter Pada Ekstrakurikuler Renang Smp Al-Muslim - Chairunissa Fajrin Batubara, Nissa; Ridlo, Azi Faiz (Motion: Journal Research of Physical Education, 2024)
Chairunissa Fajrin Batubara 41182191200091. This thesis is entitled “The Effect of Arm Muscle Power Training on 50 Meter Freestyle Swimming Speed at Estrakurikuler Swimming Smp Al-Muslim”. Physical Education Health and Recreation Study Program. Faculty of Teacher Training and Education, Islamic University 45 Bekasi. The purpose of this study was to determine the effect of arm muscle power training on 50-meter freestyle swimming speed in Al-Muslim Junior High School swimming extracurricular members. The method used in this study was experimental using a one group pretest-posttest design. The population used in this study were members of the Al-Muslim Junior High School Swimming Extracurricular. The sampling technique used purposive sampling technique with this technique, the number of samples obtained was 10 members of the Al-Muslim Junior High School Swimming Extracurricular. From statistical calculations, it can be seen that the value of the data obtained from the arm muscle power test shows the average results of the pretest 40.27 and posttest 37.01, and for the difference in test results which is 3.26. It can be seen from the results of the T test with the value of T count 9.31> T Table 1.833 and a significant value of α = 0.05%. The results of the study indicate that there is a significant effect of arm muscle power training on 50 meter freestyle swimming speed at Al-Muslim Junior High School swimming extracurriculars.